2011
DOI: 10.1016/j.ejvs.2011.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Reprinted Article “Exercise Training Versus Angioplasty for Stable Claudication. Long and Medium Term Results of a Prospective, Randomised Trial”

Abstract: Exercise training confers a greater improvement in claudication and maximum walking distance than PTA, especially in patients with disease confined to the superficial femoral artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Long-term benefits in functional performance have been demonstrated previously for SET 18 -20 , as well as for ER 21,22 , in cohort studies; the only randomized clinical trial (RCT) published so far found no significant difference in walking capacity between SET and ER 23 . However, that study did not show any increase in MWD or PFWD after approximately 6 years, possibly due to the limited number of patients.…”
Section: Discussionmentioning
confidence: 88%
“…Long-term benefits in functional performance have been demonstrated previously for SET 18 -20 , as well as for ER 21,22 , in cohort studies; the only randomized clinical trial (RCT) published so far found no significant difference in walking capacity between SET and ER 23 . However, that study did not show any increase in MWD or PFWD after approximately 6 years, possibly due to the limited number of patients.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, Perkins et al demonstrated that the long-term impact of treadmill training on MWD in patients with PAD is comparable to percutaneous transluminal angioplasty (PTA) after approximately 6 years of follow-up. The effectiveness of supervised treadmill training depended mostly on the location of the occluded artery [22]. However, in our study, the population was not evaluated in this respect.…”
Section: Walking Abilitiesmentioning
confidence: 87%
“…However, the longer‐term efficacy of these interventions in patients with IC is unknown. There are very few contemporary randomized trials reporting patient‐oriented outcome data beyond 1 year and the results of these are conflicting. Invasive treatment strategies for IC are therefore controversial.…”
Section: Introductionmentioning
confidence: 99%